Penyelesaian Kasus Perbuatan Curang Pengalihan Air Sawah Subak Puspa Sari Banjar Taman, Desa Tuwed, Kecamatan Melaya Jembrana - Ni Made Ratna Suwari; I Nyoman Gede Sugiartha; Luh Putu Suryani (Warmadewa Press, 2022)
The role of Pekasah and Traditional Villages in resolving cases of fraudulent acts of diversion of subak rice fields in Banjar Taman, Tuwed village, Jembrana Malay sub-district. Subak is a farmer community organization that lives and develops in a community that manages and regulates rice fields where this subak adheres to the concept of tri hita karana. The purpose of this research was to determine the role of Pekaseh in resolving cases of fraudulent acts of diversion of rice field water in Subak Puspa Sari Banjar Taman in Tuwed Village, District Melaya Jembrana in terms of a positive legal perspective and the role of Customary Law in resolving cases of fraudulent water diversion in subak Puspa Sari Bnajar Taman in Tuwed Village, Melaya Jembrana District. Adat in taking action based on the prevailing customary village Awig-awig. Then the type of research used in this paper is empirical is a type of field research, namely examining the applicable legal provisions and what happens in reality in society. The results of this research indicate that water problems usually occur in the famine or dry season, even though the village of Tuwed has utilized two dams, namely the Palasari dam and the Tukadaya dam, sometimes if the dry season is quite long it can also result in a decrease in the amount of water, but in the agricultural field it increases the amount of use. water because the soil is dry automatically the soil absorbs more water, at this time sometimes conflicts occur between farmers who want to use water for their respective agriculture, what if there has been a prolonged conflict that disrupts the harmony in the community, the traditional village is obliged to take a decision and steps to resolve problems that occur.